Whole genome sequencing of Priestia megaterium isolated from the gut of sea cucumber (Holothuria leucospilota) - Darren Dean, Tay; Mei-Yen, Choo; Siti Munirah, Musa; Hajar Fauzan, Ahmad (Elsevier Ltd, 2023)
Priestia megatrium represents a bacterium of interest in a wide application of the field of biotechnology. Often it is sought after for its ability that boasts great rate for biosynthesis production of smaller biological molecules while also representing a suitable host to generate compounds such as cobalamin. The bacterium can also be found in a wide variety of habitats including sea water. Sea cucumbers have begun to be quite popular to a point of extinction in certain species. This interest could be associated to the uniqueness attributed to its gut microbiome or just the organism itself. Nevertheless, the presence of Priestia megaterium within the gut of Holothuria leucospilota might serve as rationale to the previous statement. Here, we describe a detailed genomic analysis of Priestia megaterium isolated from the gut of Holothuria leucospilota. Genomic DNA was extracted from nutrient broths which were incubated with pure cultures of Priestia megatrium which were previously isolated from the sea cucumber. Whole genome sequencing was carried out using an Oxford Nanopore Technology platform which used a long-read protocol. The study reported a complete genome of Priestia megatrium compromising of 5,323,711Â bp genome size with a GC content of 37.9Â . Finally, the annotated genome was submitted to the NCBI database. Overall, this study revealed the complete genome of Priestia megatrium and would serve to potentially explain its association towards the gut microbiome found within Holothuria leucospilota.